2022
DOI: 10.4103/apc.apc_46_22
|View full text |Cite
|
Sign up to set email alerts
|

Functional and morphometric changes in children after neonatal arterial switch operation for transposition of the great arteries

Abstract: Background: The increase in the survival of patients with D-Transposition of the great arteries (TGA) after arterial switch operation (ASO) has now turned our focus to the evaluation of mid and long-term outcomes. Although most patients are followed by conventional echocardiography, the study of cardiac functionality and morphometric parameters in children with TGA after ASO is scarce. The present study aims to describe the functional and morphometric echocardiographic changes in children after AS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
0
0
0
Order By: Relevance
“…The presence of reduced LV function after ASO has been demonstrated by several studies. Some have shown that young patients after ASO can exhibit preserved LV systolic function with only subtle abnormalities in myocardial mechanics [12,[24][25][26]. Other studies showed that alterations in ventricular function can occur after ASO, particularly in the right ventricle (RV) [19].…”
Section: Imaging Modalities For Assessing Cardiac Mechanicsmentioning
confidence: 99%
“…The presence of reduced LV function after ASO has been demonstrated by several studies. Some have shown that young patients after ASO can exhibit preserved LV systolic function with only subtle abnormalities in myocardial mechanics [12,[24][25][26]. Other studies showed that alterations in ventricular function can occur after ASO, particularly in the right ventricle (RV) [19].…”
Section: Imaging Modalities For Assessing Cardiac Mechanicsmentioning
confidence: 99%